Effect of long-term rotation on astigmatism following EVO-toric intraocular collamer lens implantation - Xun Chen; Xun Chen; Xun Chen; Xun Chen; Huamao Miao; Huamao Miao; Huamao Miao; Huamao Miao; Mingrui Cheng; Mingrui Cheng; Mingrui Cheng; Mingrui Cheng; et al. (Frontiers in Medicine, 2023)
ObjectiveTo evaluate the effect of long-term rotation on astigmatism following Evolution-toric intraocular collamer lens (EVO-TICL) implantation.MethodsForty eyes of 22 patients were enrolled in this prospective study. Visual acuity, refractive parameters, and axial position of the EVO-TICL by OPD-Scan III aberrometer were measured preoperatively, 1 month and 3 years postoperatively.ResultsLast visit, the safety index was 1.32 ± 0.15 and the efficacy index was 1.01 ± 0.23. The best-fitting curve of the attempted versus achieved correction was y = 0.9751x + 0.001. The mean spherical equivalent (SE) decreased from −8.94 ± 2.72D preoperatively to 0.06 ± 0.24D and − 0.36 ± 0.46D 1 month and 3 years postoperatively, respectively. The mean target and surgical induced astigmatism were 1.55 ± 0.61D and 1.67 ± 0.94D 3 years postoperatively. The average expected axis of the TICL was-1.15 ± 9.07 (−21–19°). One month and 3 years postoperatively, the average actual axis was −0.70 ± 9.86 (−20–20°) and − 0.35 ± 11.72 (−25–30°), respectively. The absolute rotation of the TICL was 3.70 ± 4.42 (0–22°) and 6.00 ± 6.70 (0–32°) 1 month and 3 years postoperatively, respectively (p < 0.001). The expected astigmatism was −0.10 ± 0.12D, and the mean actual astigmatism was −0.21 ± 0.30D and − 0.44 ± 0.45D 1 month and 3 years postoperatively, respectively. The mean absolute rotation without postoperative astigmatism was 3.73 ± 2.69 (0–9°) and 1.67 ± 1.66 (0–5°) for low (<2D) and high (≥2D) astigmatic TICL, respectively (p < 0.05).ConclusionEVO-TICL implantation is safe and effective, with good predictability and stability. OPD-Scan is a fast device to detect the axial position of the TICL without mydriasis, and the axial position is relatively stable in the long term postoperatively. A slight rotation of low-astigmatic TICL may not cause postoperative astigmatism, whereas rotation of the high-astigmatic TICL may cause it.